Spinoza..: Men are deceived if thety think themselves free - Popkin, Richard H. 1923-2005 (Richard Henry) (Oneworld, 2004)
Popkin reconstructs Spinoza the man, and his theories, contrasting these findings with some of the popularity held misconceptions.